3D Holey Graphene/Polyacrylonitrile Sulfur Composite Architecture for High Loading Lithium Sulfur Batteries. Issue 16 (11th March 2021) - Wang, Tao; Zhang, Qiusheng; Zhong, Jiang; Chen, Maoxin; Deng, Hongli; Cao, Jinhui; Wang, Lei; Peng, Lele; Zhu, Jian; Lu, Bingan
Abstract: Lithium sulfur (Li–S) batteries have attracted considerable interest as next‐generation high‐density energy storage devices. However, their practical application is limited by low capacity and rapid capacity fading at commerical‐level mass loadings, which is largely attributed to the inferior electron/ion conduction, as well as severe the shuttling effect of soluble polysulfide species. To address these issues, a three‐dimensional holey graphene/polyacrylonitrile sulfur (3DHG/PS) composite cathode is developed for high‐mass‐loading Li–S batteries. The unique architectural design with the 3D holey graphene framework ensures fast electron and ion transport within the thick electrode, and affords enough space for mitigating the volume expansion of the electrode. Moreover, in situ Raman results demonstrate that covalent sulfur within 3DHG/PS fundamentally avoids forming soluble lithium polysulfides, which effectively reduces the undesired shuttling effect. With these advantages, the 3DHG/PS cathode exhibits an ultra‐low capacity fading rate of 0.012% per cycle after continuous 1500 cycles, as well as high specific capacity and superior rate capability with a high mass loading of 15.2 mg cm –2, which offers a promising avenue to construct future Li–S batteries with superior performance at mass loadings that exceed commercial levels. Abstract : A covalent sulfur‐based polyacrylonitrile sulfur composite is embedded in a 3D holey graphene framework to construct a high‐mass‐loading lithium–sulfur battery cathode. The 3D holey graphene framework can highly improve electron conduction, significantly shorten ion transport path, achieving fast ion conduction, which results in excellent electrochemical performance at mass loadings that exceed commercial levels.